2000
DOI: 10.1128/aem.66.2.735-738.2000
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic, Host Specificity, and Molecular Characterization of a HungarianCryptosporidium meleagridisIsolate

Abstract: This study was undertaken in order to characterize Cryptosporidium meleagridis isolated from a turkey in Hungary and to compare the morphologies, host specificities, organ locations, and small-subunit RNA (SSU rRNA) gene sequences of this organism and other Cryptosporidium species. The phenotypic differences between C. meleagridis and Cryptosporidium parvum Hungarian calf isolate (zoonotic genotype) oocysts were small, although they were statistically significant. Oocysts of C. meleagridis were successfully pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(23 citation statements)
references
References 33 publications
(29 reference statements)
0
22
0
1
Order By: Relevance
“…Nor were there apparent differences in animals experimentally infected with TU1867 compared to those infected with C. parvum genotype 1 (piglets and calves) (1), or genotype 2 (pigs, calves, and mice) (27). We do not believe that propagation of TU1867 in piglets had influenced the spectrum of infectivity to other animal species, as other investigators have been able to infect a range of animals with C. meleagridis (21). While natural infections with C. meleagridis have not been reported so far in chicken, rodents, cattle, or swine, the infectivity (number of oocysts required to induce infections) and virulence (intensity of infection or disease and distribution in the gut) suggest that they are more than likely to occur, much as seen in humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nor were there apparent differences in animals experimentally infected with TU1867 compared to those infected with C. parvum genotype 1 (piglets and calves) (1), or genotype 2 (pigs, calves, and mice) (27). We do not believe that propagation of TU1867 in piglets had influenced the spectrum of infectivity to other animal species, as other investigators have been able to infect a range of animals with C. meleagridis (21). While natural infections with C. meleagridis have not been reported so far in chicken, rodents, cattle, or swine, the infectivity (number of oocysts required to induce infections) and virulence (intensity of infection or disease and distribution in the gut) suggest that they are more than likely to occur, much as seen in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Our data supports and extends previous reports describing host-range studies. Darabus reported the passage of one C. meleagridis isolate originally isolated from chickens into mice, rabbits, rats, and cattle (6), and later, Sreter et al (21) reported the passage of a second isolate from turkeys into mice then into chickens.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Cryptosporidium meleagridis was originally isolated from a turkey and has subsequently been found in other avian species, including parrots, red-legged partridges, and chickens. [6][7][8][9] The infection has been experimentally established in immunosuppressed mice, 9,10 and C. meleagridis isolated from a human has been successfully passaged in chickens, mice, gnotobiotic piglets, and calves. 11 In those animals, the infectivity and virulence of C. meleagridis was similar to that of C. parvum .…”
Section: Introductionmentioning
confidence: 99%
“…meleagridis was first described in turkeys (10). In 1999, Xiao et al (11) amplified and sequenced the complete C. meleagridis small subunit (SSU) rRNA gene, and later Sréter et al (12) combined the traditional classification methods with studies of host specificity and SSU rRNA gene sequence similarity to confirm its taxonomic status.…”
mentioning
confidence: 99%